A nyílt innováció egyik eszköze Living Lab? - Füzi Anita (SZTE Gazdaságtudományi Kar közleményei, 2013)
2003-ban jelent meg a Harvard Egyetemen Henry Chesbrough professzor könyve a nyílt innovációról. A nyílt innováció olyan tudatos szemléletváltást jelent, mely lehetővé teszi a külső tudáshoz való hozzáférést a vállalakozás saját innovációs tevékenységének elősegítése érdekében. Annak ellenére, hogy könyve főleg a csúcstechnológiát alkalmazó nagyvállalatokkal foglalkozott, a nyílt innováció érvényessége kiterjed a kis- és középvállalkozások világára egyaránt. Napjaink talán legérdekesebb nyílt innovációs ökoszisztémája, mely struktúrát és irányítást ad ahhoz, hogy a felhasználó aktívan részt vegyen az innovációs folyamatban, a Living Lab elnevezést kapta. A tanulmány célja, hogy bemutassa a nyílt innováció és a Living Lab elméleti hátterét, valamint annak KKV-kra gyakorolt jótékony hatását a Botnia Living Lab példáján keresztül. In the year 2003 a book by Professor Henry Chesbrough was published with the title “Open Innovation: The new imperative for creating and profiting from technology”. Open innovation is the use of purposive inflows and outflows of knowledge in order to accelerate internal innovation, and expand the markets for external use of innovation, respectively. Despite of the fact that his book dealt mostly with large high-tech companies, the lessons of open innovation have been extended to the realm of SME as well. One of the most important recent trends is integrating users into the innovation process where value is co-created. For that purpose, the use of Living Labs has emerged as a novel form of creating competitive advantages. The Living Lab collaboration is an open innovation environment in a real-life setting, in which userdriven innovation is fully integrated within the co-creation process of new services, products and societal infrastructures. The paper therefore aims to clarify the theoretical background of open innovation and Living Labs. Furthermore, conclusions are drawn on the possibilities of small-and medium sized companies (SMEs) in Living Lab environments through the example of Botnia Living Lab.